Elimination of tumor hypoxia by eribulin demonstrated by (18)F-FMISO hypoxia imaging in human tumor xenograft models - Zhao, Songji (EJNMMI Res, 2019)
BACKGROUND: Eribulin, an inhibitor of microtubule dynamics, shows antitumor potency against a variety of solid cancers through its antivascular activity and remodeling of tumor vasculature. (18)F-Fluoromisonidazole ((18)F-FMISO) is the most widely used PET probe for imaging tumor hypoxia. In this study, we utilized (18)F-FMISO to clarify the effects of eribulin on the tumor hypoxic condition in comparison with histological findings. MATERIAL AND METHODS: Mice bearing a human cancer cell xenograft were intraperitoneally administered a single dose of eribulin (0.3 or 1.0 mg/kg) or saline. Three days after the treatment, mice were injected with (18)F-FMISO and pimonidazole (hypoxia marker for immunohistochemistry), and intertumoral (18)F-FMISO accumulation levels and histological characteristics were determined. PET/CT was performed pre- and post-treatment with eribulin (0.3 mg/kg, i.p.). RESULTS: The (18)F-FMISO accumulation levels and percent pimonidazole-positive hypoxic area were significantly lower, whereas the number of microvessels was higher in the tumors treated with eribulin. The PET/CT confirmed that (18)F-FMISO distribution in the tumor was decreased after the eribulin treatment. CONCLUSIONS: Using (18)F-FMISO, we demonstrated the elimination of the tumor hypoxic condition by eribulin treatment, concomitantly with the increase in microvessel density. These findings indicate that PET imaging using (18)F-FMISO may provide the possibility to detect the early treatment response in clinical patients undergoing eribulin treatment.